Prevalence of hypertension in relation to anthropometric indices among secondary adolescents in Mbarara, Southwestern Uganda - Godfrey Katamba; David Collins Agaba; Richard Migisha; Agnes Namaganda; Rosemary Namayanja; Eleanor Turyakira (BMC, 2020)
Abstract Background Studies investigating the prevalence of hypertension and its correlation with anthropometric indices among adolescents are still scarce compared to those conducted in adults of greater than 40 years. So far, no other study estimating the prevalence and correlates of hypertension among adolescents in Uganda has been found. Objective The purpose of this study, therefore, was to asses the prevalence of hypertension and its correlation with anthropometric indices among adolescents in Mbarara Municipality, southwestern Uganda. Methods A cross-sectional study was carried out among 616 secondary school adolescents aged 12-19 years in Mbarara Municipality, Uganda. Blood pressure and anthropometric indices were determined by standard methods. In the statistical analysis, linear regression analysis was done to assess the relationship between blood pressure and anthropometric indices. Results Overall prevalence of hypertension among adolescents was at 3.1% (n = 19) while prehypertension was 7.1% (n = 44). There was a statistically significant correlation between blood pressure, neck circumference, waist to hip ratio and body mass index at bivariate analysis. In multivariate analysis for anthropometric indices and sex, only neck circumference remained significantly correlated with blood pressure (p < 0.05). Conclusion The prevalence of hypertension among adolescents in the study setting was low. An increase in neck circumference results in an increase in blood pressure among adolescents.